NutritionDay: 10 years of growth. Issue 5 (October 2017) - Schindler, Karin; Pichard, Claude; Sulz, Isabella; Volkert, Dorothee; Streicher, Melanie; Singer, Pierre; Ljungqvist, Olle; Van Gossum, Andre; Bauer, Peter; Hiesmayr, Michael
Summary: Background & aims: Despite high prevalence at hospital admission, disease related malnutrition (DRM) remains under recognized and undertreated. DRM is associated with increased morbidity, hospital readmission rate, and burden for the healthcare system. The compelling need to increase awareness and knowledge through an international survey has triggered the launch of the nutritionDay (ND) concept. Methods: ND is a worldwide annual systematic collection and analysis of data in hospital wards, intensive care units and nursing homes. ND is based on questionnaires to systematically collect and analyze the patient's characteristics, food intake and nutrition support, as well as the determinants of their environment (facility, health care personal, etc …). Questionnaires, outcome documentation sheets and step-by-step guidance are available as download in 30 languages. Results: ND has described the nutritional status and behavior of over 150, 000 hospitalized patients and nursing home's patients in over 56 participating countries. These data allowed a local, regional, national and international benchmarking at different levels (i.e. type of medical pathologies, care facilities, etc.) and over time. Sixteen peer-reviewed publications have already been released and picture the international scene of DRM. Conclusion: This review presents the 10-year of the ND project development and shows how ND serves all health care professionals to optimize nutrition care and nutrition related structures. ND keeps progressing and is likely to become a standard tool for determining the nutritional status and behavior of hospitalized patients and nursing home's population.